2016
DOI: 10.18632/oncotarget.10876
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of FOXF2 as new predictor of poor prognosis in stage I non-small cell lung cancer

Abstract: BackgroundForkhead box F2 (FOXF2) is relatively limited to the adult lung, but its contribution to non-small cell lung cancer (NSCLC) prognosis is unclear.ResultsFOXF2 mRNA levels in NSCLC were lower than that in paired normal lung tissues (P = 0.012). The FOXF2low patients had shorter survival time than the FOXF2high patients (P = 0.024) especially in stage I (P = 0.002), chemotherapy (P = 0.018) and < 60 age groups (P = 0.002). Lower FOXF2 mRNA levels could independently predict poorer survival for patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 41 publications
2
26
0
Order By: Relevance
“…FOXF2 exhibits inhibitory effects in most tumours. In lung cancer (except for non-small cell lung cancer 20,21 ) and RMS in mice 35 , FOXF2 mainly shows a promotive effect. In HCC 23 and breast cancer 18,19 , the effect of FOXF2 can be to inhibit and to promote.…”
Section: General Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…FOXF2 exhibits inhibitory effects in most tumours. In lung cancer (except for non-small cell lung cancer 20,21 ) and RMS in mice 35 , FOXF2 mainly shows a promotive effect. In HCC 23 and breast cancer 18,19 , the effect of FOXF2 can be to inhibit and to promote.…”
Section: General Descriptionmentioning
confidence: 99%
“…Multiple studies have shown that FOXF2 can have roles in breast cancer 18,19 , lung cancer [20][21][22] , hepatocellular carcinoma (HCC) [23][24][25] , colorectal cancer (CRC) [26][27][28][29] , prostate cancer (PC) [30][31][32] , gastric cancer (GC) 33 , ovarian cancer (OC) 34 , rhabdomyosarcoma (RMS) in mice 35 and other tumours (Table 1). However, FOXF2 can both promote and inhibit proliferation, invasion and metastasis in tumours, depending on the type or subtype of the tumour.…”
Section: Introductionmentioning
confidence: 99%
“…FOXF2 was found to be associated with the development of multiple tumors. Kong et al [ 6 ] demonstrated that FOXF2 was a new independent predictive factor of non-small cell lung cancer. Its lower expression could lead to poor prognosis of patients, especially for patients with stage I non-small cell lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In epithelial cells, these transcriptional factors are directly involved in the expression of cyclin dependent kinase inhibitors and CDKN2A gene under the control of TGFβ [ 46 , 47 ]. Both downregulation of anti-apoptotic targets as well as activation of proliferative metabolism have been observed as mechanisms contributing to MAPKi-R. Downregulation of FOXF2 has been shown to promote cancer progression, EMT, and metastatic invasion [ 48 ]. In contrast, a different member of the FOX family, the stem cell transcription factor forkhead box D3 (FOXD3) has been identified as an adaptive mediator of the response to MAPK pathway inhibition selectively in mutant BRAF melanomas [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%